Immune Recovery Uveitis: Pathogenesis, Clinical Symptoms, and Treatment. (24th June 2014) - Urban, Beata; Bakunowicz-Łazarczyk, Alina; Michalczuk, Marta
Abstract : IRU is the most common form of immune reconstitution inflammatory syndrome in HIV-infected patients with cytomegalovirus retinitis who are receiving highly active antiretroviral therapy (HAART). Among patients with CMV in the HAART era, immune recovery may be associated with a greater number of inflammatory complications, including macular edema and epiretinal membrane formation. Given the range of ocular manifestations of HIV, routine ocular examinations and screening for visual loss are recommended in patients with CD4 counts <50 cells/ μ L. With the increasing longevity of these patients due to the use of HAART, treatment of IRU may become an issue in the future. The aim of this paper is to review the current literature concerning immune recovery uveitis. The definition, epidemiology, pathophysiology, clinical findings, complications, diagnosis, and treatment are presented.